2023
DOI: 10.7759/cureus.44774
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice of First Aid for Epistaxis Among the General Population in the Jazan Region of Saudi Arabia

Naif K Mahzara,
Abdullah A Mawkili,
Khalid Muafa
et al.

Abstract: Background Epistaxis, or nosebleeds, is a widespread medical condition that can be effectively managed with appropriate first aid. Understanding the general public's knowledge and practices about this is crucial. Objectives This study sought to evaluate the awareness and practice regarding first aid for epistaxis within the general population of the Jazan region in Saudi Arabia. Methods A cross-sectional survey was administered from April through June 2023… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Each correct answer is given a score of one, and the maximum score is 12. The designed Arabic version of the questionnaire was prepared by reviewing the relevant literature [8][9][10], and a panel of experts in emergency medicine, first aid, and public health ensured its content validity to measure what it is intended to measure. The experts provided feedback on the relevance and clarity of the questions, and any raised concerns have been made accordingly.…”
Section: Data Collection and The Related Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Each correct answer is given a score of one, and the maximum score is 12. The designed Arabic version of the questionnaire was prepared by reviewing the relevant literature [8][9][10], and a panel of experts in emergency medicine, first aid, and public health ensured its content validity to measure what it is intended to measure. The experts provided feedback on the relevance and clarity of the questions, and any raised concerns have been made accordingly.…”
Section: Data Collection and The Related Toolmentioning
confidence: 99%
“…Recognizing the need for first aid management, parents must understand the steps involved in stopping the bleeding and providing comfort to their children. Recent studies have shown that while parents are generally aware of first aid measures for epistaxis, their knowledge and confidence in executing these measures remain suboptimal [ 8 , 9 ]. In a cross-sectional study conducted at government primary healthcare centers in Al-Madinah Al-Munawwarah, a province in Saudi Arabia, findings revealed that only 27.9% of parents accurately responded when asked about the correct course of action to take for a case of epistaxis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in Makkah, Saudi Arabia, revealed that the overall knowledge of proper epistaxis first aid was poor, with only 437.1% participants demonstrating good knowledge ( 14 ). Similarly, another study revealed significant gaps in the knowledge and practices of first aid for epistaxis among the general population in the Jazan region, Saudi Arabia ( 15 ). In another study in Riyadh, Saudi Arabia, the general public’s practices and knowledge were found to be adequate.…”
Section: Introductionmentioning
confidence: 99%